Web Monitoring Temperature Ruangan berbasis Arduino Uno R3 dengan Fuzzy Logic - Deddy Prayama -; Deni Satria -; Amelia Yolanda -; Roni Putra - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
This study aims to develop a prototype system of control and monitoring of temperature, humidity and light automatic room with fuzzy logic-based Arduino Uno Rev. 3. The prototype built will be able to perform the function of monitoring the temperature of the room, light and moisture. This function can be accessed through the web pages and the internet, simultaneously displayed on the outdoor walls of the data center with 20x2 LCD size.